Determining the duration of a construction project using Markov chain - Ladnykh, Irene A.; Ibadov, Nabi; Beycioğlu, Ahmet (Archives of Civil Engineering, 2026)
In this article, practical application of the Markov chain to estimate the timeframe of a construction project is proposed. This methodology involves forecasting the duration of work based on the probability of transitions between different states in the implementation of the construction project. In this context, each state can represent a specific phase of the construction work, such as the different condition during construction work with or without risks. Transition probabilities between these states can be determined based on statistical data from previous projects, expert opinions, and other sources. In this article, the transition probabilities between states were established based on expert opinions. The proposed approach allows predicting the likely completion time of the project and assessing the impact of multiple elements on the project's timeframe on its duration. The article also includes numerical examples illustrating the operation of the proposed approach. The obtained results demonstrate the practical application possibilities in terms of efficient planning of a construction project considering risk factors.